Experimental testing and system identification of the sliding bistable nonlinear energy sink implemented to a four-story structure model subjected to earthquake excitation. (1st December 2022) - Chen, Yang-Yang; Su, Wei-Te; Tesfamariam, Solomon; Qian, Zhi-Chao; Zhao, Wei; Shen, Chao-Yong; Zhou, Fu-lin
Abstract: Bistable nonlinear energy sink system has been explored as an efficient vibration absorber in many areas. This paper aims to experimentally validate the seismic mitigation performance of sliding bistable nonlinear energy sink (SBNES) for multi-story building structures. An SBNES device was designed and placed on top of a four-story building structure model. Earthquake ground motions were applied through a shake table as the base excitation input into the structure model. By matching the time history envelope curves between the experiment and numerical simulation, the structural parameters of the primary structure, as well as the constitutive model of the SBNES, were experimentally determined. The comparisons between mitigated and unmitigated structural responses, including inter-story drift, acceleration, base-shear force and base-overturning moment of the primary structure, show that substantial reduction of structural seismic responses can be achieved by the SBNES device. The 1:1 transient internal resonance is verified as the dominant scheme for highly efficient targeted energy transfer. With respect to variation of peak ground acceleration, a relatively optimal interval distributed near the borderline of intra-well and inter-well regime is proposed for robust SBNES design. The test validates the potential of the SBNES strategy for both acceleration and displacement control of multi-story building structures. Highlights: The seismic mitigation performance of a sliding bistable nonlinear energy sink is investigated by shake table tests. The numerical model is calibrated by a proposed method based on matching of time history envelope curves. The experimental and numerical results demonstrate the effectiveness and robustness of the SBNES control system. A relatively optimal interval near the borderline of intra-well and inter-well regime is preferred for SBNES design.